(untitled) (Swiss Medical Weekly, 2021)
Preeclampsia is a major cause of maternal and fetal morbidity and mortality. Early recognition of the disease may be challenging. Complications may precede the onset of clinical symptoms and medical intervention is often delayed. Moreover, in the absence of specific clinical signs, many patients will present symptoms mimicking the disease without ever being diagnosed with preeclampsia. This situation may, however, lead to medical interventions and cause unnecessary stress for the patient. For many years, research tried to evaluate the significance of serum biomarkers as early indicators of preeclampsia. Among many, the sFlt-1/PlGF ratio, given its performance, aroused the greatest interest. This article reviews current knowledge on the subject, focusing on a Swiss perspective.